Principles and Practice of Behavioral Assessment - Haynes, Stephen N. (Applied Clinical Psychology,, 2000)
Behavioral assessment is a psychological assessment paradigm that emphasizes empirically supported, multimethod and multi-informant assessment of specific, observable behaviors and contemporaneous causal variables in the natural environment. The behavioral assessment paradigm stresses the use of well-validated assessment instruments and assumptions that social/environmental, cognitive, and physiological variables are often important sources of behavior variance. The behavioral assessment paradigm has had a major influence on the field of psychological assessment. It has affected the way research on the causes of behavior disorders is conducted, the way treatment processes and outcomes are evaluated, and the way treatment decisions are made. The goal of this book is to present the characteristics and underlying assumptions of the behavioral assessment paradigm and to show how they affect the strategies of behavioral assessment. Although all of the concepts and strategies discussed in this book are applicable in the research, this book focuses on the use of behavioral assessment to guide clinical judgements.